Characteristics of women with different perinatal depression trajectories. Issue 7 (5th February 2019) - Wikman, Anna; Axfors, Cathrine; Iliadis, Stavros I; Cox, John; Fransson, Emma; Skalkidou, Alkistis
Abstract: Maternal perinatal depression (PND), a common mental disorder with a prevalence of over 10%, is associated with long‐term health risks for both mothers and offspring. This study aimed at describing characteristics related to background and lifestyle, pregnancy, delivery, and postpartum of different PND trajectories defined according to the onset of depressive symptoms. Participants were drawn from a large population‐based cohort study in Uppsala, Sweden ( n = 2, 466). Five trajectory groups of depressive symptom onset were created using the Edinburgh Postnatal Depression Scale ≥13 (pregnancy) or ≥12 points (postpartum): (a) healthy (60.6%), (b) pregnancy depression (8.5%), (c) early postpartum onset (10.9%), (d) late postpartum onset (5.4%), and (e) chronic depression (14.6%). In multinomial logistic regressions, the associations between trajectories and the included characteristics were tested using the healthy trajectory as reference. Background characteristics (younger age, lower education, unemployment) were primarily associated with pregnancy depression and chronic depression . Characteristics associated with all PND trajectories were smoking prior to pregnancy, migraine, premenstrual mood symptoms, intimate partner violence, interpersonal trauma, negative delivery expectations, pregnancy nausea, and symphysiolysis. Nulliparity, instrumental delivery, or a negative delivery experience was associated with early postpartum onset . Postpartum factors (e.g., infantile colic, lack of sleep, low partner support, and bonding difficulties) were associated with early and late postpartum onset together with chronic depression . The findings suggest that different PND trajectories have divergent characteristics, which could be used to create individualized treatment options. To find the most predictive characteristics for different PND trajectories, studies with even larger and more diverse samples are warranted. Abstract : Depressive symptoms during and after pregnancy were assessed with the Edinburgh Postnatal Depression Scale. Based on symptoms above clinical cut‐offs for depression, five distinct groups could be distinguished with different levels of depressive symptoms from during pregnancy through six months after childbirth. The associations were then tested between a number of background‐ and lifestyle‐, pregnancy‐, delivery‐, and postpartum‐related characteristics and these trajectory groups.